Suppression of NK cell-mediated immunosurveillance by IL-35 drives tumor progression in EGFR-mutant non-small cell lung cancer - Li, Na; Zhang, YinSong; Zhang, XiaoJie; Wang, HaiZhi; Yang, Fang; Zhou, FengJu; Wang, DaQing; Zhang, Yan (Frontiers in Oncology, 2025)
BackgroundInterleukin-35 (IL-35) is an added member of the IL-12 heterodimeric cytokine family, composed of two subunits: EBI3 and P35 subunits, implicated in tumor immune evasion. This study investigates the expression and immunosuppressive role of IL-35 in epidermal growth factor receptor (EGFR)-mutant non-small cell lung carcinoma (NSCLC), with a focus on its interaction with natural killer (NK) cells.MethodsEighty-two NSCLC tissue samples (47 EGFR-mutant and 35 wild-type) were assessed for IL-35 expression via immunohistochemistry (IHC) targeting EBI3 and P35. ELISA, Western blot, and PCR validated protein and mRNA expression in fresh tissues (n = 14). The degree of NK-cell infiltration was evaluated as the percentage of NKp46-positive cells among CD45-positive cells. Peripheral NK cells were isolated from healthy donors and subjected to IL-35 treatment. Functional assays included CCK8, flow cytometry for CD3-CD56+ cells and NKG2D, ELISA for cytokine secretion, and cytotoxicity assays on NSCLC cell lines. In vivo, H1975 and PC-9 xenograft models with EGFR-sensitive mutations were used to assess the effects of IL-35 on tumor growth and NK-cell infiltration.ResultsIL-35 was significantly overexpressed in EGFR-mutant NSCLC tissues, with strong concordance between EBI3 and P35(r = 0.795, P < 0.0001). High IL-35 expressions associated with larger tumor size (χ2 = 16.140, P = 0.000) and EGFR mutation status (χ2 = 4.843, P = 0.028). IL-35 expression levels were associated with patient prognosis in both the overall population and the EGFR-mutant subgroup (Kaplan–Meier, P < 0.05).IL-35 expression inversely correlated with NKp46- cell density (r = -0.526, P = 0.000). The percentage of NKp46-positive cells among CD45-positive cells differed significantly between mutant and wild-type NSCLC tissues (t=-9.083,P=0.000). IL-35 inhibited NK cell proliferation and function in vitro, reducing CD3-CD56+ cell proportion (F = 101.3, P < 0.0001), NKG2D expression (F = 49.29, P = 0.0002), and cytokine secretion (IFN-γ, F = 252.388, P = 0.000, Perforin, F = 39.372, P = 0.000, Granzyme, F = 1001.822, P = 0.000); Conditioned medium from IL-35-treated NK cells enhanced proliferation, invasion, and migration of NSCLC cell lines. In vivo, IL-35 promoted tumor growth, while IL-35 neutralization reduced tumor size. The proportion of NKp46+ cells among CD45+ cells differed significantly across the control, IL-35, and IL-35 neutralizing antibody groups (One-way ANOVA, P = 0.000). The in vivo results in mice indicated that IL-35 expression remained inversely related to NKP46 expression (r = -0.753, P = 0.000).ConclusionIL-35 is upregulated in EGFR-mutant NSCLC and mediates immune suppression by impairing NK cell activity. Targeting IL-35 may offer a therapeutic avenue to restore NK cell function and enhance anti-tumor immunity.